Virgin kraft pulp and paper characteristics of Vitex Pubescens Vahl. (Halban) wood - Masrol, Shaiful Rizal; Shariffudin, Nornatasha; Adnan, Sharmiza; Irwan Ibrahim, Mohd Halim; A Hamid, Mokhtar (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Insufficient wood-based materials due to environmental sustainability have further enhanced the search for alternatives in the paper industry. Thus, wood sample from Vitex Pubescens Vahl (Halban) was evaluated based on the pulp characteristics; and paper physical, mechanical and optical properties as alternative raw material for papermaking. The wood chips were chemically Kraft cooked. Laboratory hand sheet with 120 gsm of grammage was produced without beating and bleached treatment. Overall procedures and tests were conducted according to the Technical Association of the Pulp and Paper Industry (TAPPI) and the Malaysian International Organization for Standardization (MS-ISO). The result shows that Halban virgin Kraft pulp recorded a value of screened yield percentage (38.6%), Kappa number (22.1), drainage time (6.44s), and Canadian Standard Freeness (555ml). Halban paper sheet has apparent density of 0.302g/cm3. In an optical analysis, brightness (19.81%) and opacity (99.5%) had been measured. Mechanical characteristic possess considerable tensile index (29.33Nm/g), tear index (6.028 mN.m2/g), burst index (1.04 kPa.m2/g), but low folding no (3). In conclusion, Halban wood could be considered as alternative wood-based material for papermaking based on its promising characteristics’ and also compatible with other wood-based material proposed by the previous study. However, more in-depth evaluation should be considered to improve the qualities of the pulp and paper made from Halban wood.